Information flow – sustainability and performance implications. Issue 8 (3rd August 2019) - Luo, Jianwen; Yu, Dayong; Jiang, Li
Abstract: We investigate horizontal and vertical information sharing in a setting, in which retailers order from suppliers and compete in quantity in selling products to a market with uncertain demand. The retailers order from the same supplier in common sourcing but from different suppliers in independent sourcing. Each retailer has access to a demand signal and can utilize it in responsive decision making. They can leverage this by sharing signals with each other (horizontal information sharing). The suppliers have no market access but can acquire the retailers' signals by offering them payments as incentives (vertical information sharing). We demonstrate that the retailers have an incentive to share signals when market competition is not intense, and this incentive is weaker when they order from the same supplier than from independent suppliers. While incentives exist for suppliers to seek information from retailers in certain conditions, vertical information sharing never emerges in the equilibrium. Sourcing structure intricately affects the interplay between the two forms of information flow. We further explore the effectiveness of horizontal information sharing as a performance-enhancing instrument for competing retailers.